2012
DOI: 10.1007/s00405-011-1850-1
|View full text |Cite
|
Sign up to set email alerts
|

Programming peculiarities in two cochlear implant users with superficial siderosis of the central nervous system

Abstract: The implants were fairly beneficial in restoring hearing and improving communication abilities although many reprogramming sessions have been required. The hurdle in programming was the need of frequent adjustments due to the physiologic variations in electrical discharges and neural conduction, besides the changes in the impedances. Patients diagnosed with superficial siderosis may achieve limited results in speech perception scores due to both cochlear and retrocochlear reasons. Careful counseling about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Screening by title and abstract excluded 2,345 studies. Full-text review excluded 126 studies, and a total of 53 publications were included in the final analysis (2,5,6,8–10,15–61). A diagram of the search process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Screening by title and abstract excluded 2,345 studies. Full-text review excluded 126 studies, and a total of 53 publications were included in the final analysis (2,5,6,8–10,15–61). A diagram of the search process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 and Table 2 summarize the findings from past reports describing the course of patients more than 3 months after surgery. While good results have been reported in many studies (Table 1), 4,[9][10][11][12][13][14][15] recent reports indicate that these are not uniformly achieved. [3][4][5][6] The patients whose data are included in Tables were described in a review by Tyler et al, 16 who concluded that unless symptoms are stable, the benefits of using CIs will probably not be maintained.…”
Section: Discussionmentioning
confidence: 99%
“…A CI revision on the right was performed in 2017 without any intraoperative complications. Intraoperative ART measurements did not show any ECAP response on the electrodes chosen for stimulation (E1, 3,7,11). The reason for that was clipping of the implant amplifier at relatively low stimulation charges, 20 nC (E3), 30 nC (E7), and 36 nC (E11).…”
Section: Casementioning
confidence: 97%
“…The cause of this form of accumulation is chronic bleeding, wherein the hemosiderin acts cytotoxically on the surrounding subarachnoid tissue [ 5 ] . The onset of clinical symptoms ranges from 14 to 77 years with a male-to-female ratio of 3:1 [ 4 , 7 ]. The causes of bleeding are in up to 50% of the cases idiopathic where no bleeding source is found and secondary forms, where a bleeding source can be detected [ 4 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation